2017
DOI: 10.1038/srep46545
|View full text |Cite
|
Sign up to set email alerts
|

Mercury pollution in vegetables, grains and soils from areas surrounding coal-fired power plants

Abstract: Mercury contamination in food can pose serious health risks to consumers and coal-fired power plants have been identified as the major source of mercury emissions. To assess the current state of mercury pollution in food crops grown near coal-fired power plants, we measured the total mercury concentration in vegetables and grain crops collected from farms located near two coal-fired power plants. We found that 79% of vegetable samples and 67% of grain samples exceeded the PTWI’s food safety standards. The merc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(77 citation statements)
references
References 48 publications
4
64
1
8
Order By: Relevance
“…In Germany [48], soil mercury levels exceeded the maximum regulation limits in bean roots and carrot shoots planted in gardens situated in the area of a mine dump. Li et al [49] reported that soil, vegetable, and grain samples collected from field locations within 10 km distance from coal-fired power plants in China, had significantly higher mercury concentrations than the samples purchased from a grocery store away from any power plant. 79 % of vegetable samples and 67 % of grain samples exceeded the upper limit of allowable mercury level.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany [48], soil mercury levels exceeded the maximum regulation limits in bean roots and carrot shoots planted in gardens situated in the area of a mine dump. Li et al [49] reported that soil, vegetable, and grain samples collected from field locations within 10 km distance from coal-fired power plants in China, had significantly higher mercury concentrations than the samples purchased from a grocery store away from any power plant. 79 % of vegetable samples and 67 % of grain samples exceeded the upper limit of allowable mercury level.…”
Section: Discussionmentioning
confidence: 99%
“…Hg pollution also arises from the nonferrous metal, coal, and cement industries, and mine-tailing waste ( Figure 1). Discharge of Hg to the atmosphere results in contamination of soil, water, and vegetation before re-release through volatilization ('latent emission') [11], with soil chemistry and groundwater characteristics directly affecting the distribution and concentration of contamination [12]. Environmental risks are determined by the bioavailability of Hg [13].…”
Section: Introductionmentioning
confidence: 99%
“…These mine sites include Poboya, Palu city (6.5 mg Hg kg -1 ) [18]; Sumalata District, North Gorontalo Regency (up to 1.31 mg kg -1 ) [17]; and Buru Island, Maluku (0.08 mg kg -1 ) [16]. Plant samples from the Kaili coal mining region, China, and the Idrija mercury mine area, Slovenia, have high average Hg contents of 0.88 and 12.7 mg kg -1 , respectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted around the power plant, China by Li, results showed that vegetable leaves contain high concentration of Hg, which collated significantly with the amount present in soils. These authors finally concluded that the long term consumption of mercury loaded vegetables would pose a health risk to the consumers [5,6].…”
Section: Introductionmentioning
confidence: 99%